Abortion in religious perspectives: Islam, Hinduism, and Buddhism - Karim, Fatimah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), IIUM, 2022)
Abortion is understood as the unnatural termination of pregnancy by the removal or expulsion from the uterus of a fetus or embryo prior to viability. Religion is a key factor that control of morality in the society today. The arguments on the morality of abortion are often based on the religious beliefs. Hence, in this study, the researcher will discuss the argument of abortion particularly in three major religions in Malaysia which are Islam, Hinduism, and Buddhism. In order to study the topic, the researcher relies on the descriptive method and analytical method. One of the important findings of the research is that abortion as seen by Islam, Hinduism, and Buddhism with each referring to their own sacred texts as a guiding foundation, did not support the abortion. However, all of these religions accept abortion as a means to save the mother's life. Thus, in order to curb the increasing number of abortions that carried out without any valid reason in nowadays secularization era, there are some measures that have to be taken seriously especially in religion, education, and cultural aspects.